PEMANFAATAN ALAT PERAGA PRAKTIK BERBASIS PENDEKATAN KONTEKSTUAL PADA POKOK BAHASAN RANGKAIAN LISTRIK DAN GETARAN - Albert Lumbu; Florentina Maria Panda (LPPM Uncen, 2021)
Learning is a complex proces, involving many component inside. One of the component that play a bigest role in learning is the teacher. Teacther has three main roles; as a designer, an executor, and an evaluator. This activity aims to 1) Give train to teacher and student to construct the props for electricity ad it vibration; 2) Develop the understanding of student regarding electricity and vibration subject; 3) Improving teachers ability to use contextual approach in physics learning. The activity conducted at SMA Yapis Nimbokranmg, Jayapura regency. Training is the method use for this activity.Keywords: : Experiment props, contextual approach, electricity and vibration